Effect of aging, cooking and freezing on tenderness, yield and microbial counts of “solomo” (outside) meat cuts. - Chacón Villalobos, Alejandro (Agronomía Mesoamericana, 2005)
A total of 115 outside cuts with a medium weight of 2.9 kg were used. Five samples were used for the estimation of the internal variation of the cut force and 10 samples for chemical composition evaluation. Eighty cuts were vacuum-packed and then aged for seven days at 7 ºC. After aging, four subgroups of 20 units were established. The first was frozen at -25 ºC for a month. The second and the third subgroups were cooked by immersion in hot water until the internal temperature reached 70 ºC. At the end of the cooking process, the third group was frozen as described above. The fourth group only underwent aging (seven days/7 °C). Twenty fresh cuts were used as a control group. The “cut force” of the 100 treated cuts was evaluated by the methods of the American Meat Science Association. Microbiological quality and weight losses of every treatment, and the pH values for fresh and aged cuts were evaluated. Fresh cuts showed high variability in tenderness, expressed as a function of the cut force estimated in 7.45 kg/cm2, and exhibited slightly higher proportion of connective tissue (2.9%). Outside fractions, both fresh and aged, showed low pH values, but did not show statistically significant differences among each other. Microbiological evaluations showed that all treatments were sanitarily executed. All treatments improved outside tenderness. The treatments composed by cooking and by freezing showed the least improvement. The best results were obtained under aging during seven days at a temperature of 7 ºC.